Design global, manufacture local: Exploring the contours of an emerging productive model. (October 2015) - Kostakis, Vasilis; Niaros, Vasilis; Dafermos, George; Bauwens, Michel
Highlights: A critique of resilient communities is used as a point of departure. We tentatively propose a global commons-oriented productive model. The proposed model could offer a viable alternative towards sustainability. A new agenda for multidisciplinary action research is introduced. Abstract: This article aims to contribute to the ongoing dialogue on post-capitalist construction by exploring the contours of a commons-oriented productive model. On the basis of this model called "design global-manufacture local", we argue that recent techno-economic developments around the emergence of commons-based peer production and desktop manufacturing technologies, may signal new alternative paths of social organization. We conclude by arguing that all commons-oriented narratives could converge, thereby supporting the creative communities which are building the world they want within the confines of the political economy they aspire to transcend.